(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2026)
Rice is a strategic commodity in Indonesia’s food system because it serves as a staple food, a source of farmers’ income, and an important component of rural economic stability. However, rice farmers continue to face several challenges in the value chain, including weak bargaining position, dependence on middlemen, limited market access, low value added at the farm level, and price fluctuations. This article aims to review literature on rice value chain analysis as an approach to strengthening farmers’ competitiveness. The method used is a literature review by examining secondary sources, including scientific articles, institutional reports, and statistical publications related to rice value chains, agricultural marketing, farmer institutions, and agribusiness competitiveness. The review indicates that farmers’ competitiveness is determined not only by farm productivity but also by access to quality inputs, market information, grain quality improvement, post-harvest handling, and strong economic institutions. An inclusive rice value chain can improve value distribution through strengthening farmer groups, cooperatives, business partnerships, digital marketing, financial access, and post-harvest infrastructure. Therefore, value chain analysis is an important instrument to identify actors, activities, margins, constraints, and strategies to improve rice farmers’ competitiveness sustainably.